2005
DOI: 10.5739/isfp.2005.420
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Design of Water Hydraulics-Motion Control and Open-Ended Solutions

Abstract: The paper presents and discusses a R&D-view on trends in development and best practise in design of both low- inexpensive, readily available and easily disposable. The low-pressure tap water hydraulic systems cover up to around 50 bar, and 2-4kW having a strong potential to compete with pneumatic and electrical solutions in many applications. The high-pressure water hydraulic systems cover typically up to 160 bar pressure from pump and to motors and actuators 140 bar. Recently, dedicated pumps and accessories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…In our previous study, it was shown that the ABW model is effective in representing the hysteresis of the muscle 16) . Equation (1) shows the discretized ABW model with time step k.…”
Section: Modeling Of Tap-water-driven Muscle and Estimation For Its P...mentioning
confidence: 99%
“…In our previous study, it was shown that the ABW model is effective in representing the hysteresis of the muscle 16) . Equation (1) shows the discretized ABW model with time step k.…”
Section: Modeling Of Tap-water-driven Muscle and Estimation For Its P...mentioning
confidence: 99%
“…The swashplate has an inclination angle which defines the stroke of the pistons. The theoretical flow of the pump is worked out with the piston area, stroke of the pistons, number of the pistons and the rotation speed of the cylinder block [8][9][10][11][12]. The valve plate realizes the connection of the piston chambers to the suction and pressure ports.…”
Section: Fig1 Water Hydraulic Axial Piston Pumpmentioning
confidence: 99%
“…Past two decades, in order to meet the demand of economic development and environmental protection, pure water hydraulic systems has been applied in food industry, steel mills, nuclear engineering, and desalination plants because pure water is environmentally friendly, non-toxic, non-flammable and cost-effective (Lim et al, 2003;Conrad, 2005). Ceramic materials are thought of the suitable materials in the water hydraulic systems.…”
Section: Introductionmentioning
confidence: 99%